Particle tracking microrheology of the power-law viscoelasticity of xanthan solutions. (December 2016) - Papagiannopoulos, Aristeidis; Sotiropoulos, Konstantinos; Pispas, Stergios
Abstract: We use particle tracking microrheology to obtain the power-law dynamical behaviour of xanthan in several aqueous solution conditions and illustrate that the probe particle motion is subdiffusive even at low xanthan concentrations. Analysis of the concentration dependence of xanthan's viscoelasticity is described in terms of linear and comb polyelectrolyte rheological models. There is a clear distinction between two power-law regimes i.e. unentangled and entangled of the modulus prefactor as a function of concentration. The critical entanglement concentration and the power-law exponents are investigated in terms of their dependence on the content and valency of the added salts. Above the entanglement concentration the deviation of the particles motion from Brownian diffusion depends strongly on concentration. Linear complex viscosity is compared to nonlinear steady shear rate viscosity in an illustration of predicting the nonlinear rheology from particle tracking measurements in food biopolymer solutions. Finally in renatured xanthan solutions the viscoelasticity enhancement by temperature treatment is demonstrated to be more effective in the entangled region. Graphical abstract: Highlights: Video particle tracking microrheology showed power-law behaviour for xanthan. Two power-law regimes in concentration are observed i.e. unentangled and entangled. Effects of content and valency of added salts are tested. Complex viscosity is compared to the steady shear rate viscosity. Renatured xanthan solutions are tested by temperature treatments.